Numerical modeling of CLT diaphragms tested on a shake-table experiment - Barbosa, Andre R. (2018)
Current standards and existing literature provide very limited information regarding the design of cross-laminated timber (CLT) floor diaphragms. In addition, limited procedures exist to develop analytical models to estimate the deformation response of CLT floor diaphragms. This paper presents a modelling approach that captures the response of CLT timber diaphragms, with a special focus on CLT spline panel-to-panel connections. The modeling approach is validated through the comparison of the results of the computation model with experimental data obtained from a series of shake-tables test performed on a two-story full-scale building tested in the summer of 2017 at UC San Diego Large High Performance Outdoor Shake Table. The two-story building included two diaphragm designs at each floor level. The first solution consists of CLT panels connected with plywood surface splines that are fastened using self-tapping screws, while the second consists of a CLT-concrete composite floor solution. Results from the nonlinear pushover analysis describe accurately the experimental data obtained.